Development of a lower-sodium oxybate formulation for the treatment of patients with narcolepsy and idiopathic hypersomnia. (1st February 2022) - Junnarkar, Gunjan; Allphin, Clark; Profant, Judi; Steininger, Teresa L.; Chen, Cuiping; Zomorodi, Katie; Skowronski, Roman; Black, Jed
ABSTRACT: Introduction: Sodium oxybate (SXB) is a standard of care for cataplexy, excessive daytime sleepiness, and disrupted nighttime sleep in narcolepsy. At recommended dosages in adults (6–9 g/night), SXB increases daily dietary intake of sodium by 1100–1640 mg. Because excess sodium intake is associated with increased blood pressure and cardiovascular risk, an oxybate formulation containing 92% less sodium than SXB (lower-sodium oxybate; LXB) was developed to provide an alternative oxybate treatment option. In 2020, LXB was approved for treatment of cataplexy or excessive daytime sleepiness in patients 7 years of age and older with narcolepsy, and in 2021, for treatment of idiopathic hypersomnia in adults. Areas Covered: Development of LXB from initial concept to regulatory approval is described, including formulation development and preclinical and clinical studies. Pharmacokinetic parameters and bioequivalence evaluations from phase 1 clinical trials are detailed. Efficacy and safety results from phase 3 clinical trials of LXB in patients with narcolepsy or idiopathic hypersomnia are presented and discussed. Expert Opinion: Reducing sodium from high sodium‒containing medications is an important step to offset cardiovascular risks associated with high sodium consumption. The development of LXB exemplifies the importance of a collaborative approach to drug development, with patient needs paramount. Plain Language Summary: Sodium oxybate (Xyrem®) is a medication for people with narcolepsy aged 7 years and older. Xyrem treats symptoms of excessive daytime sleepiness (EDS) or cataplexy (attacks of muscle weakness caused by emotion) in narcolepsy. At the recommended dosages in adults, Xyrem adds a large amount of sodium to daily dietary intake. Too much sodium in the diet is associated with increased blood pressure and risks of damage to the heart and blood vessels. Researchers used calcium, magnesium, and potassium ions in addition to a small amount of sodium to make a new oxybate medication, called Xywav®, that has 92% less sodium than Xyrem. Xywav and Xyrem were similar in laboratory and animal studies. In people, the body absorbs and processes Xywav slightly differently than Xyrem, but Xywav treatment has been shown to work the same to reduce symptoms of cataplexy and EDS in people with narcolepsy and is approved by the US Food and Drug Administration. Another neurological disorder with EDS is called idiopathic hypersomnia. Based on a clinical study, Xywav also reduced EDS and other symptoms in people with idiopathic hypersomnia. Side effects with Xywav are similar to those seen in previous studies with Xyrem.